Protective effect of caffeine against cyclophospha mide induced in vivo genotoxicity (Journal of Laboratory Animal Science, 2018)
Cyclophosphamide is a DNA non-intercalating agent with wide application against several human neoplasms.  It is found that caffeine alters protection against cytogenotoxicity of different chemicals and physical mutagens  including cyclophosphamide. Modulation of the clastogenic induced effect of cyclophosphamide by three  different doses of caffeine (25, 50 and 100 mg/kg) was assessed through the chromosomal aberration and  mitotic index studies in bone marrow cells. Micronucleus level were decreased significantly (28.8%) in 100 mg  caffeine treated group at 30 h post treatment. Results revealed that caffeine decreased the cyclophosphamide  induced chromosomal aberration and mitotic index in bone marrow cells. In the present study, the percentage  of dividing cells were reduced more in the mice pre-treated with CAF at the dose rate of 100 mg/kg than  with lower doses of CAF in all the three anticancer drugs tested. Thus, CAF modulation is expected to play  an important role in the development of cancer chemotherapy. The protective effect of caffeine was found to  be dose dependent. However, further study on the mechanism of quenching of free radicals and induction of  apoptosis by caffeine are required to substantiate the results.
Keywords: caffeine; chromosomal aberration; cyclophosphamide; cytogenotoxicity; mitotic index